EVALUACIÓN FINANCIERA EN LA EMPRESA ALMACENES JUAN EL JURI YAMAHA LOJA CORRESPONDIENTE A LOS PERIODOS 2012 – 2013 EN LA CIUDAD DE LOJA - Maldonado Gamboa, Ángela Verónica (2016)
The main motivation of this work is to contribute to the company Almacenes Juan Eljuri "Yamaha Loja" for the periods 2012 - 2013 in the city of Loja ", since according to the diagnosis of the economic situation of the company, points were found weak the same that can be overcome through the implementation of the Financial evaluation helps improve their development in the market; so that the research was conducted in compliance with the following objectives: Apply the financial evaluation using the DuPont system and financial indicators Almacenes Juan Eljuri "Yamaha Loja"; The specific objectives: To determine the current economic situation, using the DuPont system to know what is the profit margin on sales, efficient use of fixed assets and investment value in the institution and use techniques of financial evaluation to determine the degree of liquidity, indebtedness and profitability. The financial structure allowed to know the participation of different industries involved in the economic and financial position of the company; are conducting a horizontal analysis increases, decreases and the distribution of the figures in the financial statements was determined; applying financial indicators liquidity, debt, profitability and business activity are met; economic and financial performance was analyzed through evaluation measures such as: The Economic Value Added (EVA), DUPONT System Value and Balance Point, the same that allowed propose alternatives for improvement that lead to increased levels of profitability and therefore achieve permanence of the company, these alternatives are reflected in a Financial Assessment report to serve as a guide to owners of the company to take corrective action. 5 The methodology used for the development of this thesis began with the collection of information that allowed us to know the state in which the entity is, starting from the particular to the general by determining the different problems faced and quantifying its operations to confirm that information; Thus using techniques reality store is known, making known its administrative, financial and economic situation. Finally, the respective conclusions where it is emphasized that the store needs economic methods such as financial evaluation, which contributes to making timely decisions establishing administrative management. Against this is recommended at least twice a year the implementation of a financial evaluation, in order to meet their economic situation and therefore make decisions based on real events and objectives for improving profitability progressively store.